Research on the quality markers of antioxidant activity of Kai-Xin-San based on the spectrum–effect relationship - Shan, Xiaoxiao; Yang, Xuan; Li, Dawei; Zhou, Lele; Qin, Shaogang; Li, Junying; Tao, Wenkang; Peng, Can; Wei, Jinming; Chu, Xiaoqin; Wang, Haixuan; Zhang, Caiyun (Frontiers in Pharmacology, 2023)
Kai-Xin-San (KXS) is one of the classic famous traditional Chinese medicine prescriptions for amnesia, which has been applied for thousands of years. Modern pharmacological research has found that KXS has significant therapeutic efficacy on nervous system diseases, which is related to its antioxidant activity. However, the antioxidant material basis and quality markers (Q-makers) of KXS have not been studied. The objective of this study is to explore the Q-makers of antioxidant activity of KXS based on spectrum-effect relationship. Specifically, the metabolites in KXS extracts were identified by UPLC-Q-Exactive Orbitrap MS/MS. The fingerprint profile of KXS extracts were established by high-performance liquid chromatography (HPLC) and seven common peaks were identified. Meanwhile, 2, 2-diphenyl-1-picrylhydrazyl (DPPH) test was used to evaluate the free radical scavenging ability of KXS. The spectrum-effect relationship between its HPLC fingerprint and DPPH free radical scavenging activity was preliminarily examined by the Pearson correlation analysis, grey relation analysis (GRA), and orthogonal partial least squares discrimination analysis (OPLS-DA). Further, the antioxidant effect of KXS and its Q-makers were validated through human neuroblastoma (SH-SY5Y) cells experiment. The results showed that 103 metabolites were identified from KXS, and the similarity values between HPLC fingerprint of twelve batches of KXS were greater than 0.900. At the same time, the results of Pearson correlation analysis showed that the peaks 8, 1, 14, 17, 18, 24, 16, 21, 15, 13, 6, 5, and 3 from KXS were positively correlated with the scavenging activity values of DPPH. Combined with the results of GRA and OPLS-DA, peaks 1, 3, 5 (Sibiricose A6), 6, 13 (Ginsenoside Rg1), 15, and 24 in the fingerprints were screen out as the potential Q-makers of KXS for antioxidant effect. Besides, the results of CCK-8 assay showed that KXS and its Q-makers remarkably reduced the oxidative damage of SH-SY5Y cells caused by H2O2. However, the antioxidant activity of KXS was decreased significantly after Q-makers were knocked out. In conclusion, the metabolites in KXS were successfully identified, and the Q-makers of KXS for antioxidant effect was analyzed based on the spectrum-effect relationship. These results are beneficial to clarify the antioxidant material basis of KXS.